Carbon dioxide sequestration on mortars containing recycled aggregates: A hot area for startup development - Mastali, Mohammad (2020)
The world is closer to exceeding the budget (cumulative amount of anthropogenic CO2 emission compatible with a global temperature-change target) for the long-term target of the Paris Climate Agreement than previously thought. Three lines of evidence suggest that global warming will be faster than projected in the recent IPCC special report.  First, greenhouse-gas emissions are still rising. Second, governments are cleaning up air pollution faster than the IPCC and most models previously assumed. But aerosols, including sulfates, nitrates and organic compounds, reflect sunlight so the aforementioned cleaning could have a warming effect by as much as 0.7 ºC. And in third place, there are signs that the planet might be entering a natural warm phase because the Pacific Ocean seems to be warming up. And these three forces reinforce each other. Carbon dioxide sequestration is therefore crucial for targets for limiting global warming. Europe is now putting great efforts and funding in carbon sequestration materials and technologies. The flagship programme EnCO2re, currently looks to develop new technologies offering novel ways to use CO2; increase awareness for CO2 re-use; and ensures sustainability and social acceptance of materials and products by integrated socio-ecological research. Also Carbon capture and sequestration is one of the 100 Radical Innovation Breakthroughs for the future (Europe, 2019)..This chapter discloses results of an investigation concerning the performance of fly ash/waste glass alkaline-based mortars with recycled aggregates reinforced by hemp fibres. The results show that hemp fibres lead to a reduction of mechanical properties of alkali-activated materials.